Design Performance Appraisal for Contractor Employee Using Behaviorally Anchored Rating Scales and Analytical Hierarchy Process Methods - Fauzi, Mukhammad Ziddan; Mukti, Yoanita Yuniati; Bakar, Abu (West Science Business and Management, 2023)
Human resources are essential for an organization's functioning and contribute to its progress by being of high quality. The quality of human resources is reflected in optimal performance. One of the activities to measure employee performance is by conducting performance appraisals. PT. Bintang Sejahtera Putra is a company engaged in fabrication services, such as mechanical contracting and electrical. The issue faced by the company is the absence of a performance evaluation system that can assess employees from both the company's and the client's perspectives. This research aims to design an employee performance appraisal system from both the company's and the client's perspectives, using the Behaviorally Anchored Rating Scale for determining critical incidents and the Analytical Hierarchy Process as a weighting method. This study results in two evaluation systems: from the company and the client. The criteria used in the company's evaluation system include job quality 12.97%, work targets 17.01%, discipline 8.86%, responsibility 6.26%, attendance 11.84%, work attitude 6.17%, cooperation 5.53%, initiative 3.07%, leadership 3.17%, and job knowledge 7.50%. Meanwhile, the criteria used in the client's evaluation system is the client perspective with a weight of 17.61%. The client's perspective criteria result in several sub-criteria, namely neatness 19.76%, satisfaction 49.05%, and service 31.19%.